2017
DOI: 10.4103/jfmpc.jfmpc_19_17
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation, etiology, management, and outcomes of iliopsoas abscess from a tertiary care center in South India

Abstract: Introduction:Iliopsoas abscess (IPA) is the collection of pus in the iliopsoas compartment. The etiology of IPA is variable and depends on the geographical area and the antibiotic usage prevalence in that area. This study attempts to evaluate the etiology, clinical features, risk factors, management modalities, and outcomes in patients with IPA from a tertiary care center in South India.Materials and Methods:This was a retrospective study done in a tertiary care center in South India. Patient details were obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
1
9
0
2
Order By: Relevance
“…5 An Indian study showed Mycobacterium tuberculosis as the commonest cause of IPA. 6 Pathogens causing primary IPA include S. aureus, coagulase negative staphylococci (CoNS), M. tuberculosis and occasionally E. coli. In secondary IPA, in addition to these, Klebsiella spp., Enterococcus spp., Proteus spp., Bacteroides spp., Peptostreptococcus spp., Clostridium spp., and Salmonella Enteritidis have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…5 An Indian study showed Mycobacterium tuberculosis as the commonest cause of IPA. 6 Pathogens causing primary IPA include S. aureus, coagulase negative staphylococci (CoNS), M. tuberculosis and occasionally E. coli. In secondary IPA, in addition to these, Klebsiella spp., Enterococcus spp., Proteus spp., Bacteroides spp., Peptostreptococcus spp., Clostridium spp., and Salmonella Enteritidis have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…An abscess in this compartment is known as an iliopsoas abscess. This usually occurs via haematogenous spread [ 7 ]. Iliopsoas abscess is a rare condition in the western world, but it is more prevalent in the south Asian region.…”
Section: Introductionmentioning
confidence: 99%
“…Iliopsoas abscess is a myositis involving the iliopsoas compartment which can be primary or secondary. Primary psoas abscess is seen due to lymphatic or vascular spread and is more common in immunocompromised individuals while secondary abscess is seen due to contiguous spread [ 1 ]. Primary infection is seen in developing countries, while secondary infection is most often seen in developed countries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Imaging modalities used for diagnosis include magnetic resonance imaging (MRI), Computed tomography (CT) scan and ultrasonography (USG). Patients can be started on empirical anti-tubercular treatment when the culture does not yield anything [ 1 ]. An active intervention in the form of percutaneous drainage (PCD) or rarely surgical drainage may be required [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation